Omics-Driven Systems Interrogation of Metabolic Dysregulation in COVID-19 Pathogenesis - Song, Jin-Wen; Lam, Sin Man; Fan, Xing; Cao, Wen-Jing; Wang, Si-Yu; Tian, He; Chua, Gek Huey; Zhang, Chao; Meng, Fan-Ping; Xu, Zhe; Fu, Jun-Liang; Huang, Lei; et al. (Cell metabolism, 2020)
The coronavirus disease 2019 (COVID-19) pandemic presents an unprecedented threat to global public health. Herein, we utilized a combination of targeted and untargeted tandem mass spectrometry to analyze the plasma lipidome and metabolome in mild, moderate, and severe COVID-19 patients and healthy controls. A panel of 10 plasma metabolites effectively distinguished COVID-19 patients from healthy controls (AUC = 0.975). Plasma lipidome of COVID-19 resembled that of monosialodihexosyl ganglioside (GM3)-enriched exosomes, with enhanced levels of sphingomyelins (SMs) and GM3s, and reduced diacylglycerols (DAGs). Systems evaluation of metabolic dysregulation in COVID-19 was performed using multiscale embedded differential correlation network analyses. Using exosomes isolated from the same cohort, we demonstrated that exosomes of COVID-19 patients with elevating disease severity were increasingly enriched in GM3s. Our work suggests that GM3-enriched exosomes may partake in pathological processes related to COVID-19 pathogenesis and presents the largest repository on the plasma lipidome and metabolome distinct to COVID-19. [Display omitted] •Quantitative lipidomic and metabolomic profiling of COVID-19 plasma•Plasma metabolite panel distinguished COVID-19 from healthy controls (AUC = 0.975)•Differential correlation analyses uncovered metabolic dysregulation in COVID-19•GM3-enriched exosomes are positively correlated with COVID-19 pathogenesis Plasma metabolite panel effectively distinguished COVID-19 patients from healthy controls (AUC = 0.975). Plasma monosialodihexosyl gangliosides (GM3s) were negatively correlated with CD4+ T cell count in COVID-19 patients, and GM3-enriched exosomes were positively correlated with disease severity. These observations suggest that GM3-enriched exosomes may participate in pathological processes associated with COVID-19 progression.